Early Permian arc-related volcanism and sedimentation at the western margin of Gondwana: Insight from the Choiyoi Group lower section - Strazzere, Leonardo (2016)
Permian sedimentary and basic to intermediate volcanic rocks assigned to the Conglomerado del Río Blanco and Portezuelo del Cenizo Formation, lower part of the Choiyoi Group, crop out between the Cordon del Plata, Cordillera Frontal and Precordillera of Mendoza Province, Argentina. The sedimentary rocks are represented by six lithofacies grouped in three facies associations. They were deposited by mantled and gravitational flows modified by high-energy fluvial currents that evolved to low-energy fluvial and lacustrine environments. They constitute the Conglomerado del Río Blanco, which cover unconformably marine Carboniferous sequences. Five volcanic and volcaniclastic facies make up the beginning of volcanic activity. The first volcanic event in the Portezuelo del Cenizo is basaltic to andesitic lava-flows emplaced in the flanks of volcanoes. Lava collapse produced thick block and ash flows. Interbedding in the intermediate volcanic rocks, there are dacites of different geochemical signature, which indicate that the development of acidic volcanism was coetaneous with the first volcanic activity. The geochemistry of these rocks induces to consider that the Choiyoi Group Lower section belongs to a magmatic arc on continental crust. The age of this section is assigned to the lower Permian (277 ± 3.0 Ma, Kungurian age).